(untitled) (Journal of Building and Road Research, 2021)
The main objective of the research presented in this paper is to conduct a physical and chemical characterization of the locally produced Electric Arc Furnace Slag (EAFS) that produced by Giad Company for Industries, and to determine the degree of its Pozzolanicity. Also the aim of the study is to explore the possibility and feasibility of using this industrial waste as a cement replacement in mortar mixes. Different percentages of cement replacement with the slag had been studied (namely 20%, 30%, 40% and 50% with the slag had been studied respectively). Chemical and physical properties of the slag were studied in accordance to the international standards (ASTM and BS) specially the American Society for Testing and Materials (ASTM C311). Chemical analysis showed that locally produced steel slag contains high amount of iron due to purification process in steel manufacturing comparing the results with standard (ACI 233). Also testing of raw materials such as fineness, loss on ignition and X-ray diffraction test (XRD) were carried out. After that the required tests on cement mortar were carried out namely; consistency test, initial and final setting times and strength test according to the standard. XRD analysis results showed presence of both crystalline and non-crystalline silica (Amorphous) which indicated good pozzolanicity of the slag. A degree of pozzolanicity of 83.4% at 28 days indicates a good quality electric arc furnace slag and a promising pozzolanic supplementary material in concrete. Compressive strength test of mortar samples in 2, 7, 14 and 28 days with different percentages of electric arc furnace slag (0%), 20%, 30%, 40% and 50% had been conducted. Finally, the study proved the efficiency and feasibility of using one of the industrial wastes as a cement replacement in concrete industry in Sudan